One size doesn't fit all: Tailoring adult antiretroviral treatment - Nathan Geffen; M Robinson; F Venter; M Low (AOSIS, 2014)
Advances in antiretroviral treatment mean that patients in the public health system can be given more options in the management of their treatment. Although public health programmes tend to offer one-size-fits-all approaches, patients might benefit from a more flexible approach. In particular, we propose that people with HIV should be given more choice with regard to when to start treatment, and patients who experience efavirenz side-effects should be encouraged to switch to other medications, which will be facilitated by faster registration and lower prices of newer antiretrovirals.